Le più antiche carte della chiesa e ospedale di S. Giacomo de Redere di Amelia (1145-1199) - Voltaggio, Mattia (Scrineum, 2013)
This paper’s purpose consists in the critical edition of the oldest documents on parchment (1145-1199) of S. Giacomo de Redere, stored in the historical archives of S. Paul’s outside the Walls Abbey. Excepted a pseudo-original, documents give evidence of several contractual typologies: we find 29 deeds of gift, 13 bills of sale, 1 security, 1 emphyteusis; furthermore, 13 exchanges of real properties, 7 restitutions of unlawfully owned properties, 1 promissio and 1 assignment of a claim. The introduction explains historical events of S. Giacomo and its archives, examining common forms of Amelia’s private deeds and comparing them with common forms used in the area of Rome and in east Umbria in the second half of XII century. Tables (rectores and priores; financial officers; Amelia’s bishops) and indexes (documents; names and place-names; scribes and judges) accompany the text.